2016
DOI: 10.1007/s10854-016-5266-y
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted synthesis of Sn(1−x)CoxO2 nanoparticles: effect of impurity phase formation on structural, optical and electrochemical properties

Abstract: Nanocrystalline Sn (1-x) Co x O 2 (x = 0, 0.01, 0.03 and 0.05) nanoparticles have been synthesized under microwave irradiation using oxalic acid (H 2 C 2 O 4 ) as reducing agent. X-ray diffraction studies show that the prepared nanoparticles are crystalline with tetragonal crystal system and with few additional phases, which is further supported by Raman spectroscopy. The variation in molar concentration of Co 2? ions had a significant effect on size and morphological aspects which is evident from high resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…These defects are accountable for the A 1g peak shift (Figure S4b) and the generation of additional vibrational bands in the spectra. The bands located at 248, 306, 341, 505, 543, and 693 cm –1 correspond to the E u (2) TO, E u (3) TO, E u (2) LO, A 2u TO, B 1u (3), and A 2u LO modes. , …”
Section: Characterizationmentioning
confidence: 97%
See 1 more Smart Citation
“…These defects are accountable for the A 1g peak shift (Figure S4b) and the generation of additional vibrational bands in the spectra. The bands located at 248, 306, 341, 505, 543, and 693 cm –1 correspond to the E u (2) TO, E u (3) TO, E u (2) LO, A 2u TO, B 1u (3), and A 2u LO modes. , …”
Section: Characterizationmentioning
confidence: 97%
“…The normal vibrational modes of the rutile tetragonal correspond to the E u (2) TO, E u (3) TO, E u (2) LO, A 2u TO, B 1u (3), and A 2u LO modes. 22,23 The elemental compositions and oxidation states of SN0 and SN7 were investigated by XPS (Figure 2a−f). Figure 2a displays the spectra of SN0 and SN7, confirming the presence of Sn, O, and Ni elements.…”
Section: Characterizationmentioning
confidence: 99%
“…Dilute magnetic semiconductors (DMSs) have received a great deal of attention recently because of the opportunity to employ the charge and spin features of electrons in the field of spintronics. DMS systems possess both semiconducting and magnetic properties, enabling them to be the suitable materials for technological applications. , The essential prerequisite for the practical application of DMS is to exhibit room-temperature ferromagnetism (RTFM), which can be easily observed in oxide nanomaterials. , The origin of induced magnetism in these systems is still a controversial subject. Some investigations have suggested that the incorporation of suitable dopants in the undoped semiconducting structure plays a crucial role in making them ferromagnetic, , whereas a few other studies have reported that mediated defects such as oxygen vacancies (V o ) are accountable for the occurrence of this phenomenon. Oxide semiconducting nanomaterials such as SnO 2 , ZrO 2 , TiO 2 , ZnO, and CeO 2 have attracted much interest from the research community because of their various potential applications. Among them, SnO 2 nanomaterials have been used in gas sensing, transparent conducting electrodes, spintronics, optoelectronics devices, flat-panel displays, and Li-ion batteries because of their unique features, such as high optical transparency, rich oxygen vacancies, good electrical conductivity, and better thermal and chemical stabilities compared with other nanomaterials. SnO 2 (n-type semiconductor) has a large energy gap ( E g = 3.6 eV). Its space group is P 4 2 / mnm , and it has a tetragonal rutile crystal lattice.…”
Section: Introductionmentioning
confidence: 99%